2011
DOI: 10.1245/s10434-011-1651-1
|View full text |Cite
|
Sign up to set email alerts
|

Closed Abdomen Hyperthermic Intraperitoneal Chemotherapy with Irinotecan and Mitomycin C: a Phase I Study

Abstract: Closed HIPEC combining MMC and irinotecan is safe and feasible. For HIPEC, the maximum tolerated dose of irinotecan is 100 mg/m(2) when used with 0.7 mg/kg MMC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…After post-chemotherapy retroperitoneal lymph node dissection in patients with testicular cancer, chylous ascites was reported in 7.0% of patients (25). In a case series of Cotte et al on 12 patients with hyperthermic intraperitoneal chemotherapy, chylous ascites occurred in one patient (26). The absolute numbers of patients and percentages may also be seen in table 2.…”
Section: Incidencementioning
confidence: 94%
See 1 more Smart Citation
“…After post-chemotherapy retroperitoneal lymph node dissection in patients with testicular cancer, chylous ascites was reported in 7.0% of patients (25). In a case series of Cotte et al on 12 patients with hyperthermic intraperitoneal chemotherapy, chylous ascites occurred in one patient (26). The absolute numbers of patients and percentages may also be seen in table 2.…”
Section: Incidencementioning
confidence: 94%
“…MCT-diet alone showed to be effective within 6 days in 75% of patients in a study by Kaas In a study by Aoki et al (14), the incidence of postoperative chylous ascites in pancreatic surgery was decreased from 7.7% to 2.9% by a so called "milk test" which involved intraoperative insertion of 100 mL Of the 36 publications analyzed, 9 described surgical revision for chylous ascites refractory to conservative therapy (5,11,15,16,18,25,26,28,36). A peritoneovenous shunt was placed in 5 publications (15,16,18,25,28), whereas 4 did not specify the performed operative procedure in detail (5,11,26,36). The use of a peritoneovenous shunt was associated with an 80% surgical revision rate in a study by Evans et al (25), and Pabst et al reported a 20% mortality (28).…”
Section: Treatmentmentioning
confidence: 99%
“…The individual reasons for the replacement of oxaliplatin by irinotecan in the IRI group are summarized in Table 1. The safety of intraperitoneal application of irinotecan has been proven in several published studies [12, 18, 19]. However, due to the lack of consistent data there are still no national and/or international standards for HIPEC regimens in patients with colorectal peritoneal metastasis [15].…”
Section: Methodsmentioning
confidence: 99%
“…The procedure of CRS and HIPEC in treating PC arising from different organs is gaining momentum with more institutions acquiring technical support and expertise in various parts of world. Reports from single institutions are published for example in 11 patients from Arizona; [5] 12 patients with irinotecan and mitomycin -Phase I study from France; [6] 20 patients from 2001 to 2008 with follow-up of 8-28 months from Spain; [7] 21 patients followed for 43 months from China; [8] 22 patients from 2007 to 2010 followed for 35 months from Croatia; [9] 26 patients from 2007 to 2011 from Mexico. [10] Peritoneal carcinomatosis is often fatal.…”
Section: Resultsmentioning
confidence: 99%